XI JINPING'S LEADERSHIP IN CHINA'S SOCIO-ECONOMIC DEVELOPMENT BLUEPRINT - Banwo, Adetoro; Okide, Uju (Malikussaleh Social and Political Reviews, 2025)
Leadership entails crafting out ideologies and formulating plans that would foster development and alleviate the problems of the society. President Xi Jinping has proffered a methodology on how to study historical phenomena and its inherent problems. His ideology was built on existing thoughts of two prominent Chinese leaders, Mao Zedong and Deng Xiaoping. This study examines the thoughts and ideas of President Xi with the aim of exposing his blueprints for the economic planning and development of China. Data obtained through typical case sampling and content analysis was used for this study. Certain factors such as economic, political, cultural, social and ecological development were selected for this study. It adopts the theory of historical materialism to comprehend this study. It ascertains that a society’s mode of production will determine its social, political and intellectual development. It argues that the political leadership of a country should engineer the socio-economic development of the citizenry by making full use of the productive forces of the economy. Thus, President Xi has highlighted 14 basic areas in which government should focus to expedite socio-economic development and progress of the nation. This work concludes that the interplay of the productive forces of the economy through the vision of the political leadership of the state can actually champion the required socio-economic development and advancement.